Body composition by bioelectrical impedance analysis and prevalence of obesity in school-age children - Salas-Flores, Ricardo; González-Pérez, Brian; Cornejo-Barrera, Judith; Llanas-Rodríguez, José Daniel; Cruz-Hernández, Cosme (Revista Médica del Instituto Mexicano del Seguro Social, 2018)
Background: the interest in the direct assessment of adiposity is increasing. The aim was to assess fat mass and lean mass by bioelectrical impedance, and to analyze the correlation between  percentage Body Fat-body mass index and percentage Body Fat-WC, and determine the prevalence of overweight and obesity in a sample of school-age children.Methods: a cross-sectional study were performed in 360 children; differences between the sexes were assessed by independent t-test. Prevalence of overweight and obesity were calculated according to body mass index and two percentage body fat-based cutoffs.Results: there was no significant gender difference in body mass index (p = 0.91), while the boys were both taller and present more abdominal obesity but with lower mean % body fat (p < 0.00). The body mass index criteria show a high prevalence for overweight and obesity in boys (12.7 % and 17.7 %) than girls (12 % and 13.9 %).Conclusions: is an urgent need to implement preventive actions among school children to decrease the of the prevalence of childhood obesity that constitutes an important health problem in Mexico.